THE IN VITRO PRODUCTION OF ANTIBODY BY DELAYED PHASE CORNEAL LIMBAL LYMPHOID FOCI - Leibowitz, Howard M. I. (The Rockefeller University Press, 1963)
The intracorneal inoculation of a sufficient quantity of a soluble protein antigen into the eye of a rabbit produces a biphasic allergic reaction in that cornea. The earlier stage, characterized by a diffuse corneal clouding, is a manifestation of delayed hypersensitivity and is accompanied by a limbal infiltrate composed predominantly of lymphocytic-mononuclear elements. The later response, known as the Wessely Phenomenon, is a ring of opacification in the cornea which is visible in the gross. This reaction is dependent upon the presence of specific circulating antibodies and is therefore classified among the immediate types of hypersensitivity. It is accompanied by a dense limbal infiltration of plasma cells. Intervening between the two reactions is a period of several days during which the eye appears relatively normal. Explants containing large numbers of infiltrating lymphocytic-mononuclear elements were removed from the corneal-scleral junction of experimental eyes during the height of the delayed type hypersensitivity reaction and maintained in vitro in tissue culture. At a later date the overlay fluid in which the explants were maintained was shown to contain specific humoral antibodies, demonstrating the capability of cells present at a delayed reaction for the later production of antibodies. The possible linkage of the two modes of immune phenomena is discussed.